Comparison of minimally invasive surgery with laparotomic approach in the treatment of high risk endometrial cancer: A systematic review. Issue 5 (May 2020) - Scaletta, G.; Dinoi, G.; Capozzi, V.; Cianci, S.; Pelligra, S.; Ergasti, R.; Fagotti, A.; Scambia, G.; Fanfani, F.
Abstract: Objective: To analyze all published studies comparing minimally invasive surgery (MIS) with laparotomic one in the surgical treatment of high-risk endometrial cancer (EC) in term of operative, peri-operative and oncological outcomes. Data sources: We conducted a systematic literature search in PubMed between January 1995–March 2019. Methods of study selection: Titles and abstracts were analyzed by two reviewers. A set of explicit criteria was used for selection of literature: 1) randomized controlled trials (RCT), prospective or retrospective cohort studies, given the rarity of this tumor and the concomitant lack of data in the form of large trials, all reviewed original report publications with an appropriate number of subjects were considered and included; 2) participants of interest being patients who have suffered from high risk EC 3) the outcome measures including overall survival (OS), disease-free survival (DFS) and recurrence, (4) English language, (5) abstract available. Results: Thirty relevant articles were selected for full reading. For final analysis 20 studies were selected. Then, as second step, the full articles were evaluated to determine whether full inclusion criteria were met. In total, 9 papers were identified and included. Conclusion: MIS appears to be safe in the management of high-risk EC patients, showing better perioperative and postoperative outcomes and comparable oncological outcomes than open surgery. Prospective randomized trial would be needed to confirm this data.